KEARIFAN LOKAL DAN BENTURAN BUDAYA ORANG INDONESIA DI NEGARA LUAR DALAM NOVEL EDENSOR KARYA ANDREA HIRATA - Fauzi Rahman; Ryan Hidayat (BAHASTRA, 2018)
Â This study aims to find out the image of the values of local wisdom and cultural clash of Indonesian people who bring the mission of nationalism in the country outside, in the novel Edensor by Andrea Hirata. The method used in this research is qualitative descriptive with content analysis technique. Content analysis technique means textually searching for words, sentences, or ideas related to the research topic to then the data obtained are presented, verified, and drawn conclusions. The results obtained from this study indicate that the aspects of local culture appear more prominent or more dominant than other aspects, followed by aspects of religion, custom, and social. The dominant aspect of local culture is that of the characters in the novel because the clearly described figures still have an awareness to defend their culture despite the onslaught of Western cultures. If this is analogous to the representation of the people of Indonesia, then this awareness that carried Edensor. The success of the characters won the bets visiting as many countries as possible to foster self-confidence and pride as the nation of Indonesia. The realization that even though Indonesia is still a moratorium, still lagging behind in science and technology, has grown awareness to dare to advance and forge itself in global competition. It is possible for this nation to change for the better, not only in the mastery of science, but also in the improvement of attitudes in maintaining local wisdom, even if it was abroad.